Strengthening Students’ Character through Tahfidz Quran in Islamic Education Curriculum - Kosim, Muhammad; Kustati, Martin; Sabri, Ahmad; Mustaqim, Mujahidil (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This article related to a character education model aims to link the orientation of intra-curricular activities and extra-curricular activities, which are typically conducted separately. In this context, the built model is not to reproduce what has been taught in intra-curricular activities, which leads to inefficiencies. It is also not as a substitution where extra-curricular activities replaced intra-curricular activities based on the assumption of distrust in the process of character formation in intra-curricular activities. The model in the form of extra-curricular activities has a role in strengthening character education efforts performed in intra-curricular activities. This rises within the Islamic studies subject and Tahfidz Quran extra-curricular activity. By building the spirit of character education, the model creates the Quran as the primary foundation to the life philosophy of Minangkabau people in West Sumatra, “Adat Basandi Syara, Syara Basandi Kitabullah.” This model is derived from the research conducted in two senior high schools: SMAN 1 Padang Panjang and SMAN 1 Padang. The research uses qualitative methodology, and data are collected through observation, interview, and documentation. The results of the study are thematically analyzed in three main categories: the reinforcement patterns of the curriculum of Islamic Studies through Tahfidz Quran activities; students’ efforts in memorizing the Quran; and the impacts of Tahfidz program initiation on students’ character.